Coeficiente de rugosidad de canales abiertos de hormigón incluyendo micro partículas de ceniza volcánica, cemento portland tipo I y He - Yaulema Llangarí, Víctor Hugo (2018)
In recent years, several academic research has been carried out, on the roughness coefficient in various parts of the world. However, there are still doubts about the precise estimation of this coefficient in concrete-lined channels for calculating the flow rate. In addition, it is not known that the mainstreaming process of nano materials such as nano-particles of silica, alumina, iron, etc., applied to the bottom coatings and walls of the channels, to reduce the value of the roughness coefficient is of recent origin. It has revolutionized the construction industry in the hydraulic field, because it helps to increase the flow of discharge; reduce the cost of construction and maintenance. In our country there is no research on the variation of the roughness coefficient applying nano and micro-materials as coatings in concrete lined channels. Therefore this research aims to know the variation of this coefficient including micro particles of volcanic ash, portland cement type IP and HE as canal coatings. Four prototypes of prefabricated fiber cement channels were prepared, covered with percentages of 15 and 25% of volcanic ash microparticles as a partial substitute for cement, with the purpose of evaluating the influence of these percentages on the variation of the coefficient of roughness suffered by these coatings and compare them to each other. As a result, partial replacement of cement by volcanic ash micro-particles reveals a decrease from 14% to 21% of the roughness coefficient with regard to the theoretical roughness of concrete finished with a metal trowel.